The Effects of Aspirin With Combined Compound Danshen Dropping Pills on Hemorheology and Blood Lipids in Middle-Aged and Elderly Patients With CHD: A Systematic Review and Meta-Analysis - Liu, Zhi; Li, Gang; Ma, Yunwei; Lin, Ling (Frontiers in Public Health, 2021)
To systematically investigate the effect of Danshen dropping pills (DSP) combined with aspirin on blood lipids and hemorheology in middle-aged and elderly patients with coronary heart disease (CHD). The databases, including the China National Knowledge Infrastructure (CNKI), Wanfang Digital Periodical System, VIP, EMbase, PubMed, Cochrane Library and CBM. Chinese search terms included compound Danshen, compound Danshen dropping pill, Danshen dropping pills, aspirin, acetylsalicylic acid, and coronary heart disease; English search terms included Fufang Danshen dropping pills, compound Danshen dropping pills, composite salvia dropping pills, and compound red-rooted salvia. RCTs were collected comparing a combination of DSP and aspirin with aspirin applied alone. Experimental studies, animal experiments, reviews, clinical studies, abstracts, conference papers, meta-analyses, and duplicates were excluded. A total of 22 randomized controlled trials (RCTs) involving 1,987 participants suffering from CHD were selected. The major indicators were TC and TG; the secondary indicators were HDL-C, LDL-C hematocrit, high shear viscosity, low shear viscosity, plasma viscosity, PAGM, and TXB2. The combination of the DSP with aspirin has some therapeutic effect on blood lipids and hemorheology in patients with CHD, but the quality of the literature is not ideal. More high-quality RCTs are still required. As a meta-analysis, the low quality of the articles included and the small number are the main limitations of this study. In future studies, each RCT study should include recognized trial design and reporting standards, appropriate outcome indicators based on international standards, allocation of concealed blindness, and effective follow-up periods.